The impact of the Change4Life Food Scanner app on children’s diets and parental psychological outcomes: a randomised pilot and feasibility study - Sundus Mahdi; Jim Chilcott; Nicola J. Buckland (BMC Public Health)
Abstract Background The Change4Life Food Scanner app raises awareness of the nutritional content of barcode-scanned packaged food through a variety of visual displays. This study investigated (1) the feasibility and acceptability of evaluating the effectiveness of the Food Scanner app in reducing children’s energy (kcal) and sugar (g) intake over a 3-month period, (2) app engagement and (3) the app’s impact on psychological outcomes. Methods Adopting a non-blinded parallel trial design, 126 parents of 4-11 year olds were randomly assigned (1:1) through block randomisation sequences into a 3-month intervention consisting of exposure to the Food Scanner app (version 1.6; [n = 62]) or no intervention (n = 64). Intervention participants were encouraged to use the app for healthier food choices when shopping. Participants completed baseline and 3-month follow-up (3MFU) measures of child dietary intake, psychological, and health economic outcomes. Dietary intake was also assessed at 1-month. The intervention arm additionally completed fortnightly app engagement measures and all participants provided feasibility feedback at 3MFU. Mixed model Analysis of Variance and independent t-tests of mean differences assessed changes in dietary intake. Descriptive analyses were conducted for all other measures. Ethical approval was obtained by the University of Sheffield Research Ethics Committee (026380). Results The study was completed by 64 (51%) of 126 participants (29 [45%] in the intervention group and 35 [55%] in the control group). Most participants (> 80%) found the study acceptable, whilst 68% of intervention participants would recommend the app to others. There was a mean difference in daily energy (kcal) intake of 18 (95% CI: -180; 217) at 3MFU, and a mean difference of 10g in sugar intake (95% CI: -3; 23), between conditions, with a greater reduction within the control condition. Average app engagement declined over the study, from 14.1 min (± 14.7) in week 2 to 6.8 min (± 11.6) in week 12. Minor differences in psychological outcomes were observed between conditions. Conclusions Despite high attrition, study procedures were deemed feasible. Low app engagement and usage barriers may have impacted app acceptability and related outcomes. Recommendations are provided for future app development and full-scale trial design. Trial registration ISRCTN12169303; 12th May 2025. Retrospectively registered.